2006
DOI: 10.1515/znc-2006-9-1008
|View full text |Cite
|
Sign up to set email alerts
|

Deoxypodophyllotoxin Content and Antioxidant Activity of Aerial Parts of Anthriscus sylvestris Hoffm.

Abstract: Deoxypodophyllotoxin content of the aerial parts of Anthriscus sylvestris Hoffm. growing at different altitudes was evaluated in comparison to the roots. The lignan accumulation in ground parts was at least double compared to aerial ones.In addition antioxidant-guided fractionation of the crude methanol extract of aerial parts was performed with the 2,2-diphenyl-1-picrylhydrazyl (DPPH) test. Active fractions contained mainly luteolin-7-O-glucoside and chlorogenic acid. Antioxidant properties of both crude extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 7 publications
0
14
0
1
Order By: Relevance
“…Separation and identification of antioxidant components by thin-layer and column chromatography and spectral analysis demonstrated that quercetin and apigenin appeared to be the main flavonoid species and rutin was one of the major quercetin glycosides [58]. Dall’Acqua et al analyzed the crude methanol extract of aerial parts and found that the antioxidant active fractions contained mainly luteolin-7- O -glucoside and chlorogenic acid [59]. Luteolin-7- O -glucoside (cynaroside) was confirmed as the dominant polyphenolic species by the work of Žemlička et al Partially wilted flowers and stems of A. sylvestris were macerated twice with acetone for 24 h. The solvent was removed under vacuum, and the low-boiling fractions were separated by hydrodistillation.…”
Section: Phytochemical Profilementioning
confidence: 99%
See 2 more Smart Citations
“…Separation and identification of antioxidant components by thin-layer and column chromatography and spectral analysis demonstrated that quercetin and apigenin appeared to be the main flavonoid species and rutin was one of the major quercetin glycosides [58]. Dall’Acqua et al analyzed the crude methanol extract of aerial parts and found that the antioxidant active fractions contained mainly luteolin-7- O -glucoside and chlorogenic acid [59]. Luteolin-7- O -glucoside (cynaroside) was confirmed as the dominant polyphenolic species by the work of Žemlička et al Partially wilted flowers and stems of A. sylvestris were macerated twice with acetone for 24 h. The solvent was removed under vacuum, and the low-boiling fractions were separated by hydrodistillation.…”
Section: Phytochemical Profilementioning
confidence: 99%
“…It has been reported that the content of deoxypodophyllotoxin is at least 2-fold higher at high than low altitudes both in aerial and in root parts of A. sylvestris . In the aerial part the content of deoxypodophyllotoxin was measured as 0.13% at 900 m and 0.33% at 1200 m. The root of the plant harvested from an altitude of 900 m contained 0.38% deoxypodophyllotoxin, compared with 0.78% in those from 1200 m [59].…”
Section: Phytochemical Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Deoxypodophyllotoxin (DPT) (Figure ) is considered to be the plant’s main lignan constituent . It has pharmacological properties such as antiproliferative, antitumor, antiviral, anti-inflammatory, antiplatelet aggregation, and antiallergic related activities in disorders including asthma. The number of studies of DPT mechanism of action against cancer cells and other pharmacological properties is growing. ,− It also has insecticidal properties. , The closely related podophyllotoxin (Figure ) is used for the semisynthesis of the cytostatic agents etoposide and teniposide. These drugs are used for the treatment of lung and testicular cancers, Ewing’s sarcoma, lymphoma, glioblastoma, and nonlymphomatic leukemia…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies focusing on the question of which factors may influence the production of DPT in A. sylvestris suggested that environmental factors highly determine the lignan profile and content. , It has also been reported that DPT content differs at least 2-fold between low and high altitudes both in aerial (0.13% dw at 900 m, 0.33% dw at 1200 m) and in root parts (0.38% dw at 900 m and 0.78% dw at 1200 m) of A. sylvestris . Different populations of A. sylvestris yielded different lignan patterns, and there was no clear genetic factor determining the lignan profiles when seeds from different locations were grown under identical conditions. , A major drawback of that study was the limited number of plants.…”
Section: Introductionmentioning
confidence: 99%